International Conference for Innovation in Biomedical Engineering and Life Sciences ICIBEL2015, 6-8 December 2015, Putrajaya, Malaysia - Ibrahim, Fatimah; Usman, Juliana; Mohktar, Mas Sahidayana; Ahmad, Mohd Yazed (IFMBE Proceedings, 2016)
This volumes presents the proceedings of ICIBEL 2015, organized by the Centre for Innovation in Medical Engineering (CIME) under Innovative Technology Research Cluster, University of Malaya. It was held in Kuala Lumpur, Malaysia, from 6-8 December 2015. The ICIBEL 2015 conference promotes the latest researches and developments related to the integration of the Engineering technology in medical fields and life sciences. This includes the latest innovations, research trends and concerns, challenges and adopted solution in the field of medical engineering and life sciences. .